1996
DOI: 10.1080/03014223.1996.9517514
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary fossil faunas, overlapping taphonomies, and palaeofaunal reconstruction in North Canterbury, South Island, New Zealand

Abstract: Some of the predator sites accumulated fauna until late in the nineteenth century.The total avian fauna for the Waikari region (including Glenmark) comprises 65 indigenous and 4 introduced species of birds. In addition, tuatara Sphenodon spp., two species of gecko Hoplodactylus spp., including the large H. duvaucelii, undetermined skinks and fish, two species of bats Mystacina spp., three rodents Mus musculus, Rattus norvegicus and (most common) Rattus exulans, and European rabbits Oryctolagus cuniculus were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 28 publications
1
103
1
Order By: Relevance
“…11). Despite markedly lower genetic diversity, E. crassus appears to have been thriving in the Eastern forests, where late Holocene fossils have been found in great abundance (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11). Despite markedly lower genetic diversity, E. crassus appears to have been thriving in the Eastern forests, where late Holocene fossils have been found in great abundance (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Bell Hill Vineyard (121) Rosslea ( (44), Glenmark (43°00′00.0″S, 172°46′50.0″E) (43), and Glencrieff (42°58′07.45″S, 172°34′01.84″E) (57). Sample sizes are in parentheses.…”
Section: Glenmark (7)mentioning
confidence: 99%
“…Worthy and Holdaway (1996) suggested that most of the moa at PV died during the driest 17 period over summer ( Figure 2) when birds might have been tempted out on to a substantially dry lake 18 bed, where a thin crust covered the "gyttja", to find water. Gizzard contents of birds from PV 19 contained seeds and fruits (Burrows et al, 1981), perhaps supporting the contention of a summer or 20 autumn deposition (Holdaway and Worthy, 1997; .…”
mentioning
confidence: 99%
“…It is rare in areas where such forests are absent, including those dominated by matai, as in Hawke's Bay (Table 8) and the eastern South Island (e.g., Worthy & Holdaway 1996). The distribution is now at least partly explicable because observations of kakapo feeding ecology have shown that they prefer rimu foliage.…”
Section: Discussionmentioning
confidence: 99%